Affinity and kinetics study of anthranilic acids as HCA2 receptor agonists. Issue 14 (15th July 2015) - van Veldhoven, Jacobus P.D.; Liu, Rongfang; Thee, Stephanie A.; Wouters, Yessica; Verhoork, Sanne J.M.; Mooiman, Christiaan; Louvel, Julien; IJzerman, Adriaan P.
Graphical abstract: Abstract: Structure–affinity relationship (SAR) and structure–kinetics relationship (SKR) studies were combined to investigate a series of biphenyl anthranilic acid agonists for the HCA2 receptor. In total, 27 compounds were synthesized and twelve of them showed higher affinity than nicotinic acid. Two compounds, 6g ( IC50 = 75 nM) and6z (IC50 = 108 nM) showed a longer residence time profile compared to nicotinic acid, exemplified by their kinetic rate index (KRI) values of 1.31 and 1.23, respectively. The SAR study resulted in the novel 2-F, 4-OH derivative (6x ) with an IC50 value of 23 nM as the highest affinity HCA2 agonist of the biphenyl series, although it showed a similar residence time as nicotinic acid. The SAR and SKR data suggest that an early compound selection based on binding kinetics is a promising addition to the lead optimization process.